Survival of Coptotermes testaceus (Isoptera: Rhinotermitidae) to Environmental Conditions (Relative Humidity and Temperature) and Preference to Different Substrates - Cesar Orlando Pozo-Santiago; Manuel Pérez-De La Cruz; Magdiel Torres-De la Cruz; Aracely De La Cruz-Pérez; Silvia Capello-García; Minerva Aurora Hernández-Gallegos; José Rodolfo Velázquez-Martínez (Sociobiology, 2020)
Coptotermes  testaceus (L.) (Rhinotermitidae) is a subterranean termite species that causes damage in urban and agricultural areas in the neotropics. Despite its economic importance,  there  are  no  studies  on  its  basic  biological  aspects  for  laboratory management and the development of strategies for its control. The objective of the present study was to evaluate the relative humidity, temperature, substrate moisture and preference to different wood substrates for the best C.  testaceus survival under laboratory conditions. For this, a range of eight relative humidity (from 9 to 100%), three temperatures (20, 25 and 30 °C), six substrates (Pinus sp, Cedrela  odorata  (L.), Cocos nucifera (L.), Eucalyptus urophylla (S. T. Blake), Haematoxylum campechianum (L.) and Tabebuia rosea [Bertol.] DC) and four substrate moistures, (0 to 60%) were tested. The results of this study indicated a significant effect of all factors on termite survival or termite preference. When tested independently, the highest survival percentage of C.testaceus was obtained with humidity of 100%, temperature of 20 °C, substrate moisture of 60% and the Eucalyptus  urophylla substrate, reaching 83.33% survival at 21 days of observation. With these preliminary assays on small termite groups, it is concluded that with the appropriate percentages of humidity, temperature and substrate and the interaction of these three factors, further research can be conducted using larger termite groups in biologically relevant conditions, in order to study various aspects of C. testaceus biology.